Microglial Engulfment of Spines in the Ventral Zona Incerta Regulates Anxiety-Like Behaviors in a Mouse Model of Acute Pain - Farzinpour, Zahra; Liu, An; Cao, Peng; Mao, Yu; Zhang, Zhi; Jin, Yan (Frontiers in Cellular Neuroscience, 2022)
Although activation of microglial cells is critical in developing brain disorders, their role in anxiety-like behaviors in pain is still vague. This study indicates that alteration of microglia’s neuronal spine engulfment capacity in ventral zona incerta (ZIV) leads to significant pain and anxiety-like behaviors in mice 1-day post-injection of Complete Freud’s Adjuvant (CFA1D). Performing whole-cell patch-clamp recordings in GABAergic neurons in the ZIV (ZIVGABA) in brain slices, we observed decreased activity in ZIvGABA and reduced frequency of the miniature excitatory postsynaptic currents (mEPSCs) in ZIVGABA of CFA1D mice compared with the saline1D mice. Besides, chemogenetic activation of ZIVGABA significantly relieved pain and anxiety-like behaviors in CFA1D mice. Conversely, in naïve mice, chemogenetic inhibition of ZIVGABA induced pain and anxiety-like behaviors. Interestingly, we found changes in the density and morphology of ZIVMicroglia and increased microglial engulfment of spines in ZIV of CFA1D mice. Furthermore, pain sensitization and anxiety-like behaviors were reversed when the ZIVMicroglia of CFA1D-treated mice were chemically inhibited by intra-ZIV minocycline injection, accompanied by the recovery of decreased ZIVGABA excitability. Conclusively, our results provide novel insights that dysregulation of microglial engulfment capacity encodes maladaptation of ZIVGABA, thus promoting the development of anxiety-like behaviors in acute pain.